English Phonetics Course: University Students’ Preferences and Expectations - Nowacka , Marta (Research in Language, 2022)
This paper examines the perspectives of Polish university students of English (n=110) on selected aspects after the pronunciation instruction they underwent during their phonetics course. It shows qualitative questionnaire results obtained by means of four open-ended statements. It sheds light on: English accent preference, reasons why they favoured and disfavoured the course and expectations from the course tutor. The students reported a positive impact of the training on their speaking and overall English/language skills, sounding native-like, good, and being understood. They admitted to disliking rules, theory of phonetics, unexpected pronunciation of words. In addition, the expected responsibilities of a pronunciation tutor comprised: correction of students’ pronunciation and helping them improve this skill. It confirms that the nativeness principle to pronunciation learning still prevails as the students wish to sound nativelike and expect the teacher to give them corrective accuracy-based feedback.